Technology adaptation and productivity of queen pineapple intercropped with peanut, corn, and taro in the Bicol Region, Philippines - Jasmin Dacillo; Joy Villagen (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2025)
Queen pineapple (Ananas Comosus) is one of the primary commodities in the Province of Camarines Norte, Philippines, and is known as the sweetest variety of pineapple. The pineapple-based farming technology package is an integrated cropping model that includes intercropping peanuts (Arachis hypogaea), corn (Zea mays), and taro (Colocasia esculenta) with Queen pineapple. The project aims to enhance the productivity of the Queen pineapple growers in Camarines Norte through the adaptation of intercropping for Queen pineapple. The 80 farmer cooperators' site from Binatagan, San Felipe, Plaridel, Caayunan of Basud; Matanlang, and Lugui of Labo; and Dagotdotan and Maisog of San Lorenzo Ruiz were clustered to ensure the market through technology demonstration and capacity enhancement trainings. As a result, intercropping of Queen pineapple + peanut + corn + taro has significantly gained an additional income as early as 4 – 5 months before harvest of the Queen pineapple, which takes 16 – 18 months’ maturity. The ROI per crop gained from peanut was Php 18, 150.00/ hectare (28%); corn was Php 82, 896. 04/ hectare (67%); taro was Php 71, 647.50/ hectare (82%); and for the queen pineapple was Php 179, 780.00/ hectare (84.59%). The overall net income increased by Php 367,468.49 (+79.49%) and yield of 42 MT/ha. The study emphasizes the advantages of intercropping, including increase productivity, enhanced resource efficiency, lower labor and chemical inputs, pest and disease control, and maximizing the area. The study concludes that using this varied farming model can result in more resilient farming methods and sustainable food security.